Legal Protection for Children in Conflict with the Law: Policy Evaluation and Reform Recommendations - Gidion Arif Setyawan; Andy Fefta Wijaya; Hermawan Hermawan; Yurizal Yurizal (Jurnal Hukum, 2025)
The protection of children in conflict with the law represent one of the primary challenges within the Indonesian legal system, particularly in Jakarta Province. This study aims to analyze the juridical implementation of protections for children involved in legal processes, focusing on existing regulations and policies in Jakarta. Employing a socio-legal and qualitative approach, the study relies on interviews with relevant stakeholders and case studies of child protection policies at the local level. The findings reveal that despite the implementation of various regulations to safeguard children's rights, juridical execution faces several obstacles, including limited resources, inconsistencies in law application, and inadequate inter-agency coordination. The study underscores the necessity to enhance policies and strengthen institutional capacity to bolster legal protections for children in conflict with the law in Indonesia. Thus, these findings contribute to advancing a more effective child protection system aligned with human rights principles.